EXAMINATION OF VICTIMS OF SHARP TRAUMA - Jakaria Zansen (Indonesian Journal of Multidisciplinary Science, 2022)
Clinical forensic medicine is one that can be applied appropriately to the section of medical practice whose scope involves the interaction between the law, the judiciary, and the police involving (generally) living people and the issuance of visum et repertum. In general, there are two types of visum et repertum, namely visum et repertum for living victims and visum et repertum for the dead. The making of visum et repertum intended as a substitute for evidence is unlikely to be present before the trial court in such circumstances. A wound is a damage to a part of the body in the form of a break in the integrity of the tissues that can occur due to mechanical hardness. The body has the resilience and elasticity of tissues based on the softness and strength of the skeleton, the strength of which exceeds the strength of the tissues Then the tissue will adjust to the existing pressure, then the event does not happen, then the event will occur injury or injury. Sharp or pointed weapons leave characteristic wounds on the body, depending on the type of weapon used. Examination and treatment of the victim of a male, aged 34 years, the general condition of the patient is good, the awareness of mentis compost has been carried out, as well as the examination of vital signs within normal limits. On examination, it was found that there was a cut on the chin to the left jaw due to sharp trauma. Based on the theory of the results of the examination and the discussion above, it is concluded that the victim experienced a sharp trauma. The wound is qualified as a moderate wound because it causes obstruction in carrying out his daily work as a factory worker in accordance with Article 351 of the Criminal Code.